2010
DOI: 10.1111/j.1467-9507.2009.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Accuracy and Behavior in Anticipating Children's Responses to Novelty: Relations to Fearful Temperament and Implications for Anxiety Development

Abstract: Previous research has suggested that mothers' behaviors may serve as a mechanism in the development from toddler fearful temperament to childhood anxiety. The current study examined the maternal characteristic of accuracy in predicting toddlers' distress reactions to novelty in relation to temperament, parenting, and anxiety development. Ninety-three two-year-old toddlers and their mothers participated in the study. Maternal accuracy moderated the relation between fearful temperament and protective behavior, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 45 publications
4
67
0
1
Order By: Relevance
“…First, we tested whether the association between age 3 and age 6 BI was influenced by PE; like BI, PE plays a prominent role in children’s exploratory behavior and reactions to novelty, and may therefore shape how children’s early inhibition unfolds over time. We also examined whether overprotective parenting contributes to the association between children’s BI assessed longitudinally in early childhood, building on the extant literature on early caregiving and the stability of BI, as well as research implicating overprotection in the relationship between BI and subsequent anxiety (e.g., Kiel & Buss, 2010). Although investigators have tested mediation models linking overprotection to the stability of BI (Kiel & Buss, 2012), to our knowledge, no one has previously examined whether parental overprotection moderates associations between children’s BI over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we tested whether the association between age 3 and age 6 BI was influenced by PE; like BI, PE plays a prominent role in children’s exploratory behavior and reactions to novelty, and may therefore shape how children’s early inhibition unfolds over time. We also examined whether overprotective parenting contributes to the association between children’s BI assessed longitudinally in early childhood, building on the extant literature on early caregiving and the stability of BI, as well as research implicating overprotection in the relationship between BI and subsequent anxiety (e.g., Kiel & Buss, 2010). Although investigators have tested mediation models linking overprotection to the stability of BI (Kiel & Buss, 2012), to our knowledge, no one has previously examined whether parental overprotection moderates associations between children’s BI over time.…”
Section: Discussionmentioning
confidence: 99%
“…This gap in the BI literature is surprising given research implicating parental overprotection and related parenting behaviours in childhood anxiety (e.g., Kiel & Buss, 2010). Indeed, moderation effects have been reported in the child anxiety literature, finding interactions between child BI and parental overprotection when predicting child anxiety (e.g., Degnan, Almas, & Fox, 2010; Murray, Creswell, & Cooper, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous research posits that depressed mothers tend to perceive their children more negatively [e.g., 44]. However, maternal perceptions have important implications for maternal behavior and the quality of mother-child interactions [45], so utilizing maternal perceptions of toddler temperament and internalizing behavior may be just as important as using objective measures of these constructs. Nonetheless, future research could investigate the current model using observational measures of toddler temperament and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have used observational methods to examine how parenting behaviors may regulate child emotional reactivity during emotion-eliciting or threatening events among samples of infants and young children, such as during immunizations, exposure to novelty, or after caregiver withdrawal during the still-face paradigm (Contradt & Ablow 2010; Crockenberg & Leerkes, 2004; Kiel & Buss, 2010; Moore & Calkins, 2004; Spinrad, Stifter, Donelan, McCall, & Turner, 2004). These studies have typically focused on positive parenting behaviors, and have shown that low levels of maternal sensitivity, support, or soothing to child distress signals is associated with greater child behavioral and physiological reactivity.…”
Section: Parenting In Emotion-eliciting Contexts During the Transitiomentioning
confidence: 99%